MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN MELALUI TABUNG ANGKA DI TK KARANG TARUNA BANJAREJO SUKODADI LAMONGAN TAHUN PELAJARAN 2024/2025 - Anisa; Ahmad Fachrurrazi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This class action research is carried out in 2 cycles. The subject of this study is group A students of Kindergarten Karang Taruna Banjarejo which totals 15 children with the object of the ability to recognize number symbols. The results of the improvement in recognizing the number symbols of group A of Karang Taruna Banjarejo Kindergarten after applying learning using the media of number tubes, the learning outcomes of students in the second cycle increased compared to the first cycle, while the success in the second cycle was: the indicator of recognizing the number symbols 1-10 in the first cycle by 34% in the second cycle increased to 93%. Indicator Mention the symbol of the number 1-10 in the first cycle by 27% in the second cycle increased to 87%. The indicator relates the number of objects to their number symbols in the first cycle by 40%, in the second cycle it has increased to 80%. For the indicator of Counting numbers 1-10 in the first cycle of 20%, in the second cycle it increased to 80%. These results have met the success determined by the average class score of 75% and the average completeness of 85%. Thus, from this research, it can be concluded that the use of numerical tube media can improve the ability of.